Multiple-parallel-protease digestion coupled with high-resolution mass spectrometry: an approach towards comprehensive peptide mapping of therapeutic mAbs - Pradhan, Gauri; Sneha, J. M.; Sonwane, Babasaheb P.; Santhakumari, B.; Rao, Alka; Kulkarni, Mahesh J. (Journal of Proteomics, 2021)
Therapeutic monoclonal antibodies (mAbs) are structurally large and complex molecules. To be safe and efficacious, a biosimilar mAb must show high similarity to its reference product in Critical Quality Attributes (CQA). mAbs are highly sensitive to protein expression, production, manufacturing, supply chain, and storage conditions. All these factors make biosimilar mAbs intrinsically susceptible for variability during production. Accordingly, several lots of references and tests are required to establish the biosimilarity of a test mAb. The primary structure is a CQA of a mAb affecting its safety and efficacy. Here, we apply peptide mapping as an analytical method to decipher the primary structure and associated modifications for a quick quality assessment of TrastuzumAb and RituximAb innovator and biosimilar. A multiple-parallel-protease digestion strategy followed by high-resolution mass spectrometric analysis consistently achieved 100% sequence coverage along with reliable detection of post-translational modifications. Additionally, the use of supporting methods such as intact mass analysis and circular dichroism helped us to decipher the primary and higher order structures of these mAbs. We identify discernible variations in the profile of the innovator and biosimilar mAbs and validate the method for quick yet deep comparability analysis of the primary structure of biosimilar mAbs sold in the market. Significance: Peptide mapping using bottom-up approach is one of the most common methods for the characterization of therapeutic monoclonal antibodies. Herein, we describe a multi-parallel-protease digestion strategy using a combination of five different proteases followed by high-resolution mass spectrometric analysis with TrastuzumAb and RituximAb as an example. This resulted in a comprehensive identification of peptides with increased reliability and identification of different PTMs. Additional supporting orthogonal methods like intact mass and higher-order structure analysis helped evaluate broader conformational properties.
Keywords: LC-MS/MS; PTM; RituximAb; Therapeutic monoclonal antibodies; TrastuzumAb

Yoga therapy attenuates the progression of diabetes - insights from proteomics and metabolomics analysis - Sonwane, Babasaheb P.; Raut, Pooja; Chitalkar, Jyotsna; Godbole, Smita; Sabnis, Shanta; Gupta, Jyoti; Santhakumari, B.; Deshpande, Mukund V.; Kulkarni, Mahesh J. (International Journal of Yoga, 2024)
<p style="box-sizing: inherit; line-height: 1.5; margin: 1.2rem 0px; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;"> Objective: Diabetes management remains challenging despite advancements in therapeutics, with many subjects developing complications. Yoga has been shown to aid diabetes management. This study investigates the impact of yoga therapy on diabetes progression, utilizing proteomics and metabolomics analyses to explore underlying molecular mechanisms. <p style="box-sizing: inherit; line-height: 1.5; margin: 1.2rem 0px; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;"> Methodology: A 3-month longitudinal study involving healthy subjects with prediabetes and diabetes was conducted. Blood glucose, glycated hemoglobin (HbA1c), lipid profile, and malondialdehyde (MDA) levels were measured before and after the yoga intervention. <p style="box-sizing: inherit; line-height: 1.5; margin: 1.2rem 0px; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;"> Results and conclusion: Healthy subjects showed no significant changes in blood glucose, lipid profile, HbA1c, or MDA levels. However, subjects with prediabetes and diabetes experienced positive changes, with decreases in HbA1c and MDA levels. Proteomics and metabolomics analyses provided insights into the molecular mechanisms by which yoga attenuates diabetes progression in subjects with prediabetes and diabetes. This study is a pioneering effort to understand the molecular basis of yoga's beneficial effects on diabetes management.